2021
DOI: 10.3390/ph14080825
|View full text |Cite
|
Sign up to set email alerts
|

Sedative and Immunosuppressive Effects of Dexmedetomidine in Transplantation

Abstract: Dexmedetomidine, an α2-adrenergic receptor agonist, is used as an anti-anxiety medication. It exerts a cholinergic effect, thereby reducing the release of tumor necrosis factor alpha (TNF-α). We hypothesized that the use of dexmedetomidine as a sedative agent in transplantation would also protect allografts. We examined our patients who underwent living donor liver transplantation. Subsequently, we generated a series of mouse models to investigate the effect of dexmedetomidine on sedation-based tolerance post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…No new clinical trial was found after searching the clinical trial registration platform ClinicalTrial.gov and WHO ICTRP. Finally, nine studies were included in the meta-analysis, with a total of 648 participants ( Choi et al, 2016 ; Fayed et al, 2016 ; Sayed and Yassen, 2016 ; Xu et al, 2016 ; Lee et al, 2020 ; Lee et al, 2021 ; Ustun et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2022 ). See Figure 1 for the combined search results.…”
Section: Resultsmentioning
confidence: 99%
“…No new clinical trial was found after searching the clinical trial registration platform ClinicalTrial.gov and WHO ICTRP. Finally, nine studies were included in the meta-analysis, with a total of 648 participants ( Choi et al, 2016 ; Fayed et al, 2016 ; Sayed and Yassen, 2016 ; Xu et al, 2016 ; Lee et al, 2020 ; Lee et al, 2021 ; Ustun et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2022 ). See Figure 1 for the combined search results.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported a decrease in the incidence of acute kidney injury [ 20 , 45 , 46 ], while others reported no renal benefits of its use [ 55 , 61 , 62 ]. Perioperative DEX in liver transplantation decreased the IRI and improved graft outcomes through its sedative and immunosuppressive effects [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEX, a widely used sedative during surgery, was approved for sedation and analgesia by the United States Drug and Food Administration in 1999 (7). Owing to its excellent advantages of sedation, analgesia, antianxiety, inhibition of sympathetic nervous excitation, cardiovascular stabilization, and prevention of postoperative delirium, DEX has been widely used in clinical anesthesia and the ICU (8,10,27,28). The contraindications of DEX mainly include 1) patients allergic to DEX, 2) pregnant, lactating women, and patients with severe heart block.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis reported that perioperative DEX infusion inhibited the release of epinephrine, norepinephrine, and cortisol and decreased the levels of blood glucose, interleukin (IL)-6, tumor necrosis factor-a (TNF-a), and CRP (5). In addition, the immune function was improved (5,28,32). Li et al ( 27) also systematically reviewed the anti-inflammatory effects of perioperative DEX administration as an adjunct to general anesthesia in 15 clinical trials and reported significant decreases in the serum levels of IL-6, IL-8, and TNF-a after DEX use.…”
Section: Discussionmentioning
confidence: 99%